“That Cross-Curricular Business”: The Engineering Design Process in Mathematics and Science Classrooms - Vomvoridi-Ivanovic, Eugenia; Lane, Tonisha; Cain, Leia; Shmad, Salam; Willis, Selene; Gaines, Jonathan (Qualitative report, 2024)
The engineering design process (EDP) is one tool teachers can use to facilitate STEM integration. As part of a larger three-year longitudinal research project regarding engineering identity development among middle school youth in a summer robotics outreach program, this study aims to understand teachers’ willingness to incorporate engineering design in their classrooms through an exploration of their perceptions of the EDP, its applications to their subject matter and classroom context, methods of enacting the EDP, and perceived challenges to and supports for doing so. We conducted a qualitative case study and drew our results from focus groups and semi-structured interviews with eight teacher participants. Participants were successful in describing the EDP and its cyclical nature. However, classroom enactment of the EDP was predominantly indirect and often used to solve non-subject-specific classroom problems. Direct enactment was limited to projects already part of the existing curriculum. Issues with instructional resources, lesson planning, time, and student background were the EDP enactment barriers most frequently noted, while supports described were all responses to the identified barriers. The EDP offers a promising way to integrate engineering with math and science. However, additional support is needed for more meaningful classroom enactment of the EDP.